SULFORAPHANE: AGEN ANTIKANKER DAN KEMOPREVENTIF POTENSIAL SEBAGAI TERAPI ALTERNATIF PADA PASIEN ACUTE MYELOID LEUKEMIA - Irfan, Akmal Jauhari; Wijaya, Valencia Hana (Essence of Scientific Medical Journal; Vol 21 No 1 (2023): Volume 21 No. 1 (Januari - Juni 2023) Essential: Essence of Scientific Medical Journal, 2023)
ABSTRACT Introduction: Acute Myeloid Leukemia (AML) is a hematological malignancy characterized by the overproduction of myeloid stem cells in the bone marrow. Although it is a rare malignancy, AML is a type of leukemia with a poor prognosis that requires more intensive treatment. Primary therapies such as induction therapy and stem cell transplantation have developed a lot, but they have weaknesses, which are expensive and have a high risk of side effects. Sulforaphane, an herbal substance from young broccoli plants, is a potential agent in treating several types of cancer. This study aimed to review the benefits of sulforaphane as its anticancer and chemopreventive potential in AML cancer patients. Discussion: In general, sulforaphane provides anticancer effects by inducing cancer cell apoptosis, ferroptosis along with the formation of anticancer immunity, myeloid cell differentiation, and control of cell proliferation. Anticancer effects have been studied by reducing miR-155 and miR-181a as AML biomarkers, followed by a decrease in the viability of AML cancer cells. The chemopreventive effect of sulforaphane works by inhibiting the cytochrome P450 drug metabolizing enzymes phase I and induces phase II through transcriptional activation of the Nrf2 gene, which is generally involved in antioxidative processes. Conclusion: Sulforaphane has been shown to have anticancer and chemopreventive effects in AML patients. However, further research is needed regarding clinical effectiveness in AML management, pharmacokinetics, side effects, drug interactions, and safe doses in AML patients. Keywords: Sulforaphane, AML, Anticancer, Chemopreventive